Reproductive health and chlamydial infection (clinical lecture) - V N Prilepskaya; E R Dovletkhanova (IP Berlin A.V., 2013)
Chlamydial infection in women may result in some complications, among which the most serious complications are pelvic inflammatory diseases, ectopic pregnancy and infertility. The highly sensitive diagnostic methods allow to detect timely pathogen and then select treatment scheme with optimal drug choice which may decrease probability of complications.